2023
DOI: 10.3390/ijms241512019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Differentially Expressed Genes in Leaves vs. Roots Subjected to Drought Stress in Flax (Linum usitatissimum L.)

Abstract: Drought stress is a common environmental challenge that plants face, severely constraining plant growth and reducing crop yield and quality. Several studies have highlighted distinct responses between monocotyledonous and dicotyledonous plants. However, the mechanisms underlying flax tolerance to abiotic stress, such as drought, remain unclear. In this study, we investigated the morphological, physiological, and biochemical characteristics and the genome-wide gene expression of oil flax and fiber flax in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…It was utilized to improve flax crops’ fiber quality and yield [ 63 , 64 ]. In the previous study, we identified differentially expressed genes and enriched pathways related to stress response, hormone signaling, and physiological characteristics, which can be applied to develop drought-tolerant flax varieties and enhance crop productivity under water-limited conditions [ 65 ]. Furthermore, in the previous report, the gene expression profiles of flax seeds during development and identified genes involved in fatty acid biosynthesis and seed storage, which are used to enhance the oil content and quality of flax seeds, are important for various industrial applications [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was utilized to improve flax crops’ fiber quality and yield [ 63 , 64 ]. In the previous study, we identified differentially expressed genes and enriched pathways related to stress response, hormone signaling, and physiological characteristics, which can be applied to develop drought-tolerant flax varieties and enhance crop productivity under water-limited conditions [ 65 ]. Furthermore, in the previous report, the gene expression profiles of flax seeds during development and identified genes involved in fatty acid biosynthesis and seed storage, which are used to enhance the oil content and quality of flax seeds, are important for various industrial applications [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress also profoundly affects plant organelles and ultrastructures, including chloroplasts, which may undergo expansion, rupture, disintegration, and alterations in plastid and starch grain number and size 5 . Furthermore, changes in antioxidant and enzyme activities occur under drought stress 6 , alongside regulating the expression of drought-resistance-related genes 7,8 . Moreover, drought stress has been documented to affect the accumulation of various osmolytes or metabolites, including glycine betaine, polyols, polyamines, and proline.…”
mentioning
confidence: 99%